2023
DOI: 10.1093/mnras/stad286
|View full text |Cite
|
Sign up to set email alerts
|

Modelling photometric reverberation mapping data for the next generation of big data surveys. Quasar accretion discs sizes with the LSST

Abstract: Photometric reverberation mapping can detect the radial extent of the accretion disc (AD) in Active Galactic Nuclei by measuring the time delays between light curves observed in different continuum bands. Quantifying the constraints on the efficiency and accuracy of the delay measurements is important for recovering the AD size-luminosity relation, and potentially using quasars as standard candles. We have explored the possibility of determining the AD size of quasars using next-generation Big Data surveys. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 108 publications
1
9
0
Order By: Relevance
“…In addition to WFD, LSST will allocate ∼10% of its observing time to five Deep-Drilling-Fields (DDFs) for a high-cadence (∼14000 visits) deep monitoring survey down to a coadded depth of ugrizy deeper than 26.5-28.5 mag (Brandt et al 2018). The accuracy of the lags can be 5% or 15% with a 2 or 5 days cadence, respectively (Pozo Nuñez et al 2023). As studied in Kovačević et al (2022), if the observational strategy for these fields has a cadence of 1-5 days and duration >9 yr, the expected number of sources, whose continuum lags can be successfully measured, is >1000 for each DDF (10 square degree) in any filter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to WFD, LSST will allocate ∼10% of its observing time to five Deep-Drilling-Fields (DDFs) for a high-cadence (∼14000 visits) deep monitoring survey down to a coadded depth of ugrizy deeper than 26.5-28.5 mag (Brandt et al 2018). The accuracy of the lags can be 5% or 15% with a 2 or 5 days cadence, respectively (Pozo Nuñez et al 2023). As studied in Kovačević et al (2022), if the observational strategy for these fields has a cadence of 1-5 days and duration >9 yr, the expected number of sources, whose continuum lags can be successfully measured, is >1000 for each DDF (10 square degree) in any filter.…”
Section: Discussionmentioning
confidence: 99%
“…The expected AD time delays are calculated following the standard thermal reprocessing scenario with its application to PRM of the AD, as outlined in Pozo Nuñez et al ( , 2023a. In brief, the energy flux radiated from the disk combines viscous heating and external irradiation from the socalled X-ray corona.…”
Section: Simulationsmentioning
confidence: 99%
“…There are proposed solutions to the AD size problem that include contamination from nearby regions, such as the BLR, which appears in the form of lines and diffuse continuum emission (DCE; Korista & Goad 2001;Lawther et al 2018;Korista & Goad 2019;Netzer 2022;Pandey et al 2023) or even other underappreciated nondisk components (Chelouche et al 2019). These components can lead to lower or higher delays depending on the relative contribution to the filters (Pozo Nuñez et al 2023a). Internal reddening due to dust near AD, and more distant host galaxy contamination further complicate luminosity determinations, potentially underestimating AD sizes (Gaskell et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…LSST will provide photometric light curves in ugrizy bands, allowing us to study the wavelength dependence of quasar lags. Kovacevic et al (2022), Pozo Nuñez et al (2023, and others found that LSST should be able to detect short lags in quasar light curves. Here, we generate mock LSST quasar light curves reprocessed with several different short and long lags.…”
Section: Introductionmentioning
confidence: 96%